Analysis of the Effect of Job Satisfaction as an Intervening Variable on Employee Performance - Umi Farida; Titi Rapini; Rizki Listyono Putro (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Employee job satisfaction is low, resulting in suboptimal performance. Another issue is the high workload not being matched with adequate compensation and a satisfactory working environment. Based on this description, the research aims to determine the effect of the working environment on employee performance, the effect of compensation on employee performance, whether job satisfaction can mediate the effect of the working environment on employee performance, whether job satisfaction can mediate the effect of compensation on employee performance, and the effect of job satisfaction on employee performance. The research subjects are employees of UD Langgeng 99 Magetan, a company engaged in bread production. The sample size for this study is 100 employees, using the statistical analysis method of Partial Least Square (PLS). The results of this study found that the working environment affects employee performance, compensation does not significantly affect employee performance, the working environment does not affect employee performance when mediated by job satisfaction, compensation significantly affects employee performance when mediated by job satisfaction, and employee job satisfaction affects employee performance.